Epidemiology of Trauma Patients Presented at Emergency Department of Trauma Center - Paudel, Santosh; Dhungana, Siddhartha; Pokhrel, Nabin; Dhakal, Gaurav Raj (Journal of Nepal Health Research Council, 2021)
Background: Emergency Department of National Trauma Center Nepal Center is the only specialized trauma care hospital in Nepal, in operation since 2012. Traumatic injury is one of the major causes for mortality worldwide. This study aims to see the epidemiology, pattern of injuries and outcome of the patients presenting to the emergency room.Methods: After getting ethical approval, we included all patients presenting to the Emergency Department with at least one injury, between Jan 2018 to Dec 2020. Informations on age, gender, mechanism of injury and outcome was abstracted for all patients presenting to the emergency department. Data were extracted from hospital database with the permission of hospital authority.Results: Total of 49991 patients presented to emergency department with different types of injuries.  Among them 7792 (14.0%) needed hospital admission. Fall and road crashes comprised almost 80% of admitted cases. Mortality was 2.1% of admitted patients, mostly with head injuries followed by multiple injuries. Conclusions: Among the patient visiting the trauma center during the study period most common mechanism of the injury were fall and road crash with head and neck injury. Majority of the patients were only managed in the ward without surgery.Keywords: Emergency care; triage; trauma care system; unintentional injury